DOI: 10.11606/t.41.2008.tde-02032009-154826
|View full text |Cite
|
Sign up to set email alerts
|

Análise cladística de Charaxinae Guenée (Lepidoptera, Nymphalidae)

Abstract: Esta tese, e o desenvolvimento de seu projeto, somente puderam ser realizados com o apoio de muitas pessoas e instituições, às quais sou eternamente grata. Ao Dr. Marcelo Duarte da Silva, pela orientação, infra-estrutura concedida e liberdade de trabalho. À Dra. Sônia Casari, pela oportunidade no ínício do doutorado, incentivo e compreensão. Ao CNPq, pela concessão da bolsa de doutorado, e à CAPES pela bolsa de doutorado-sanduíche. Ao Programa de Pós-graduação em Zoologia do IB/USP e ao Museu de Zoologia, onde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 12 publications
5
6
0
Order By: Relevance
“…This is also in accordance with a recent cladistic analysis of morphological characters for the subfamily Charaxinae (Marconato 2008), in which, except for Anaeomorpha splendida, Preponini is monophyletic. At the generic level, Archaeoprepona and Prepona were polyphyletic, since Archaeoprepona should include the monotypic genus Noreppa, and Prepona should include Agrias, to be monophyletic.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is also in accordance with a recent cladistic analysis of morphological characters for the subfamily Charaxinae (Marconato 2008), in which, except for Anaeomorpha splendida, Preponini is monophyletic. At the generic level, Archaeoprepona and Prepona were polyphyletic, since Archaeoprepona should include the monotypic genus Noreppa, and Prepona should include Agrias, to be monophyletic.…”
Section: Introductionsupporting
confidence: 92%
“…However, the ML tree (not shown) did not recover Archaeoprepona as monophyletic at any level. Prepona was found to be paraphyletic because it included Agrias in both the NJ and the ML trees, a result supported by a previous cladistic analysis (Marconato 2008). The PreponaAgrias group did not show the same topology in the NJ and the ML analyses, but the same lower groups were recovered by both analyses.…”
Section: Preliminary Phylogenetic Reconstructionsupporting
confidence: 69%
See 1 more Smart Citation
“…D’Abrera, 1987; DeVries, 1987; Neild, 1996), and has remained moderately stable since Rydon's (1971) morphology‐based higher classification of the Charaxinae. Nevertheless, several studies have suggested that this classification is in need of revision (Furtado, 2008; Marconato, 2008; Escalante et al , 2010), but to date studies of Preponini have only been performed as part of higher‐level studies of butterflies, with relatively few preponine species represented. Based on partial sequences of the nuclear gene wingless , and with only a single preponine species included, Brower (2000) assessed the phylogenetic relationships among the tribes of the family Nymphalidae, and found Preponini to be sister to all other charaxines.…”
Section: Introductionmentioning
confidence: 99%
“…In a later work, Freitas & Brown (2004) proposed a phylogenetic hypothesis of the family Nymphalidae based on morphology, again including only one Preponini individual, Archaeoprepona chalciope (Hübner). Later, Marconato (2008) presented a phylogeny of Charaxinae based on morphological characters, including the tribe Preponini, which was represented by 13 species. This study provided strong evidence of the need for further taxonomic study of the tribe.…”
Section: Introductionmentioning
confidence: 99%